Comparison of growth performance, non-specific immunity, and intestinal microbiota of olive flounder (Paralichthys olivaceus) fed with extruded pellet and moist pellet diets under field conditions in South Korea - Jang, Won Je; Hasan, Md. Tawheed; Choi, Wonsuk; Hwang, Soyeon; Lee, Yein; Hur, Sang Woo; Lee, Seunghan; Lee, Bong-Joo; Choi, Youn Hee; Lee, Jong Min (Frontiers in Microbiology, 2022)
A 6-month feeding trial was conducted to compare the effects of extruded pellet (EP) and moist pellet (MP) feed on the growth performance, non-specific immunity, and intestinal microbiota of olive flounder. A total of 60,000 fish with an average weight of 70.8 ± 6.4 g were divided into two groups and fed with one of two experimental diets. At the end of a 6-month feeding trial, the weight gain and specific growth rate of the fish fed with the MP diets were significantly higher than those of fish fed with EP (P < 0.05). However, the EP group exhibited a lower feed conversion rate than the MP group, meaning that the EP diet was more cost-effective. Whole-body proximate compositions and non-specific immune responses (superoxide dismutase, myeloperoxidase, and lysozyme activity) were not significantly different between the two groups. There were no significant differences in the α-diversity of the intestinal bacterial community of the two groups. However, the composition of microorganisms at the phylum to genus level was different between the groups. The EP group was rich in Actinobacteria, Corynebacterium, Bacillus, and Lactobacillus, whereas the MP group was dominated by Proteobacteria, Vibrio, and Edwardsiella. Collectively, the MP diet increased growth performance and pathogen concentration in the gut; whereas EP improved feed conversion and beneficial Bacillus and Lactobacillus proportion in the intestinal microbial community.